2017
DOI: 10.1002/eap.1607
|View full text |Cite
|
Sign up to set email alerts
|

A pesticide paradox: fungicides indirectly increase fungal infections

Abstract: There are many examples where the use of chemicals have had profound unintended consequences, such as fertilizers reducing crop yields (paradox of enrichment) and insecticides increasing insect pests (by reducing natural biocontrol). Recently, the application of agrochemicals, such as agricultural disinfectants and fungicides, has been explored as an approach to curb the pathogenic fungus, Batrachochytrium dendrobatidis (Bd), which is associated with worldwide amphibian declines. However, the long-term, net ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 73 publications
3
30
0
Order By: Relevance
“… 164 However, exposure of tadpoles to any of these fungicides at field relevant concentrations, even those used to control Bd infections, resulted in higher Bd abundances and greater Bd-induced mortality. 164 Moreover, a field survey revealed that Bd prevalence was positively associated with concentrations of fungicides in ponds. 164 …”
Section: Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“… 164 However, exposure of tadpoles to any of these fungicides at field relevant concentrations, even those used to control Bd infections, resulted in higher Bd abundances and greater Bd-induced mortality. 164 Moreover, a field survey revealed that Bd prevalence was positively associated with concentrations of fungicides in ponds. 164 …”
Section: Effectsmentioning
confidence: 99%
“… 164 Moreover, a field survey revealed that Bd prevalence was positively associated with concentrations of fungicides in ponds. 164 …”
Section: Effectsmentioning
confidence: 99%
“…Fungicides are chemical substances used for control and treatment of fungal diseases of plants. The employment of fungicides has become widespread in recent decades in agriculture since it was estimated that fungal infections reduce yields of the crops worldwide by nearly 20% [1]. Fungicides have become the primary means of fungal disease control due to their relatively low cost, ease of use and efficiency [2].…”
Section: Introductionmentioning
confidence: 99%
“…to be explained in the present system. Using a combination of experiments and field surveys,Rohr, Brown, Battaglin, McMahon, and Relyea (2017) observed that low concentrations of the fungicides azoxystrobin, chlorothalonil, and mancozeb were directly toxic to Bd in culture and exposure to fungicides in the larval host stage increased Bd loads in the terrestrial host stage. We call for additional empirical studies to be conducted to test for the effects of pesticides on infection prevalence across host species to determine whether or not differential effects of pesticides according to host life stages are capable of driving patterns of infections.Second, we caution against assuming that the lack of relationships between Bd prevalence and insecticide and fungicide is evidence that these pesticide types do not influence Bd distributions.…”
mentioning
confidence: 99%
“…For instance, similar results of a decreased risk of Bd infection in the larval stage and an increased risk of Bd infection in the terrestrial stage have been associated with fungicides. Using a combination of experiments and field surveys,Rohr, Brown, Battaglin, McMahon, and Relyea (2017) observed that low concentrations of the fungicides azoxystrobin, chlorothalonil, and mancozeb were directly toxic to Bd in culture and exposure to fungicides in the larval host stage increased Bd loads in the terrestrial host stage. Field surveys found that Bd prevalence in the terrestrial life stage was positively associated with measured fungicide concentrations in pond water.…”
mentioning
confidence: 99%